2018
DOI: 10.1287/inte.2018.0966
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Continuous Flow in the Cabinet Process at the Schneider Electric Plant in Tlaxcala, Mexico

Abstract: This work presents the development and improvements obtained by the implementation of continuous flow in the cabinet process at Schneider Electric's manufacturing plant in Tlaxcala, Mexico. The areas involved were the demand-planning, materials-planning, and manufacturing processes and warehouse operations. The implementation process, which consisted of shared planning, analysis of control operations, and synchronization of lean manufacturing techniques, led to increased communication among personnel within de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This in turn had other effects such as determining the necessary workforce, which allowed the company in the case study to save 3% of costs for the year. In the same way, [4], showed that aggregate planning can reduce costs in the company. This was possible thanks to the fact that inventory was reduced, customer services were improved by 5%, stockouts and delays were reduced.…”
Section: A Aggregate Planningmentioning
confidence: 90%
“…This in turn had other effects such as determining the necessary workforce, which allowed the company in the case study to save 3% of costs for the year. In the same way, [4], showed that aggregate planning can reduce costs in the company. This was possible thanks to the fact that inventory was reduced, customer services were improved by 5%, stockouts and delays were reduced.…”
Section: A Aggregate Planningmentioning
confidence: 90%
“…It is essential to align the demand planning by reducing the variation of the demand estimate and leveling the demand, establishing EOQ to determine the optimum lot size to produce to minimize the ordering and logistic costs of maintaining the inventory, also optimizing equipment change over times allows reducing the number of Kanban cards which results in a reduction of storage space such as the transport of materials by creating a continuous flow in the value chain and making timely deliveries to the customer [11].…”
Section: Literature Reviewmentioning
confidence: 99%